Abelmoschus Esculentus (Moench.) Seed Derived Flavonoids Antioxidant Protect the Heart Against Experimental Oxidative Injury - Anjorin O. Atinuke; Komolafe, O. Aderibigbe; Ogunlade O; Anjorin O. Andrew; Saka, O. Stephen; Odukoya, S. Ayodeji (International Journal of Human Anatomy, 2020)
Since oxidative stress impairs the cardiovascular function, the hypothesis from the present study is that the treatment of paraquat-exposed adult Wistar rats with methanolic extract of Abelmoschus esculentusseed would reduce paraquat-induced cardiovascular damage. Thirty healthy female Wistar rats weighing 120-150 g were randomly assigned into 6 groups of 5 rats each (Groups A, B, C, D, E and F). Rats in groups A served as control and received normal saline while groups B, C, D, E and F received a single dose of paraquat (7mgkg-1i.p.). Rats in group B was sacrificed 24hours following paraquat administration while daily administration of 100 mg kg-1and 200 mg kg-1 of methanolic extract of Abelmoschus esculentusseed extract were given orally to groups C and D while group E received daily oral dose of Vitamin E at 100mgkg-1 and group F was left untreated. Histological and biochemical preparations of the heart was made and data were expressed as mean± SEM. Significant difference was set at p<0.05. Results showed no significance difference (p<0.05) in nitric oxide activity, Glutathione reductase activity, and troponin I activity across the paraquat-exposed groups when compared with control. Histological studies reveal distortion of normal cardiac histo-architecture in paraquat-exposed group B compared with control rats while Abelmoschus esculentus reversed these changes in other treated groups. The study concluded that paraquat caused significant distortion of the cardiac histo-architecture and methanolic extract of immature Abelmoschus esculentus seed had antioxidant and ameliorative effects similar to Vitamin E on paraquat-induced myocardial injury.
Keywords: Paraquat